SOME FUNGAL INFESTATIONS OF DRIED FISHES IN COCHIN MARKET - GUPTA, RANU; SAMUEL, C T (Fishery Technology, 2017)
Dried fish constitutes a regular item of trade in India, particularly in the interiorparts far away from the sea and rivers. The poor section of the society is the main consumer. The quality of dried fish never receives much attention at any stage of processing (drying) and storage. A good amount of these fish is discarded during drying due to fungal growth to avoid the danger of mycotoxin production.